Mediators and moderators in voluntary turnover intention: a scoping review in the public service - Silva, Ana Cláudia A. M.; Neiva, Elaine R.; Damasceno, Daniel Pereira; Ferreira, Felipe Orsini F. B. (Frontiers in Psychology, 2025)
BackgroundRecent meta-analyses present the main predictors of voluntary turnover intention (VTI) and propose the investigation of mediators and moderators as a way to enhance the explanation of the relationship.ObjectivesThis study conducts a scoping review of the main moderating and mediating variables in studies on VTI, focusing on the public servants in the executive branch. The review aimed to fill gaps by including more studies from developing and Asian countries, identifying the main mediating and moderating variables that can help explain VTI from the initial thought to the actual departure. Method: The PRISMA protocol for scoping reviews was followed. Online database searches were conducted to identify empirical articles published in the last 20 years, from which 51 publications were selected.ResultsForty-five different variables were identified, grouped into six different dimensions: (a) motivation, attitudes, and behaviors related to work; (b) person-organizational context relationship; (c) organizational characteristics and context; (d) personal conditions related to work; (e) human resource management practices; and (f) demographics. Moderating variables were found in 15 studies, mediating variables in 26 studies, and 10 studies evaluated both relationships.ConclusionSeven variables showed a complete mediating effect, which can strongly contribute to explaining the path leading to VTI. These variables are person-organization fit, goal clarity, intrinsic motivation, organizational prestige, leader-member exchange, job satisfaction, and organizational support. Additionally, important moderators related to human resource management practices were detected. Human Resources (HR) departments within public sector organizations can leverage the key mediating and moderating variables from this review to periodically assess employee turnover and VTI.